Sosialisasi dan Pengembangan Pemahaman Anak Sekolah Dasar di Kelurahan Lembah Damai Mengenai Gadget dan Media Sosial sebagai Upaya Peningkatan Karakter Anak di Era Covid-19 - Silvia Permatasari; yessy elvrina sipayung; windya fitranelda; Valiqa Vanindya; Dhea Crisanda; Nur Afifah Dzakkiyah; M. Ryanda Jaya Putra; Onni Yesika Hutabarat; Rachmia Ayunda; Aloysius Simorangkir (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Field Work Lecture (KKN) is a learning process routine for college student by providing them a real learning experience live outside campus in the midst of society and identify and deal with problems that are being faced by the community directly. This educational counseling activity purposes is to bring elementary school students from Lembah Damai Village to understand about one of our work program purposes which is literation. In this research there are several understandings given and a review of the literature from various sources regarding the character of post-covid-19 students. This activity purposes are for elementary school students in Lembah Damai Village to have an understanding of wisely using gadgets and social media as well as character development after the pandemic of COVID-19. This activity are done in two ways which are counseling and showing an educational video on how to improve literacy skills for students. The result of this community dedication are to increase knowledge and skills of students at SDN 64 Pekanbaru and SDN 102 Pekanbaru.